The valuation treadmill how securities fraud threatens the integrity of public companies - Park, James 1975- (Cambridge University Press, 2022)
Public companies now face constant pressure to meet investor expectations. A company must continually deliver strong short-term performance every quarter to maintain its stock price. This valuation treadmill creates incentives for corporations to deceive investors. Published more than twenty years after the passage of Sarbanes-Oxley, which requires all public companies to invest in measures to ensure the accuracy of their disclosures, The Valuation Treadmill shows how securities fraud became a major regulatory concern. Drawing on case studies of paradigmatic securities enforcement actions involving Xerox, Penn Central, Apple, Enron, Citigroup, and General Electric, the book argues that corporate securities fraud emerged as investors increasingly valued companies based on their future performance. Corporations now have an incentive to issue unrealistically optimistic disclosure to convince markets that their success will continue. Securities regulation must do more to protect the integrity of public companies from the pressure of the valuation treadmill